Inkompatibilitas Sosial dalam Pemberlakuan Aturan Perkawinan di bawah Tangan Pada Masyarakat Plural di Kecamatan Katibung Lampung Selatan - Azima Amalia; Nurnazli Nurnazli; Abdul Qodir Zaelani (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
This study aims to analyze the social incompatibility in the implementation of unregistered marriage (nikah siri) regulations within a plural society, focusing on the readiness of state legal instruments, socio-cultural factors, and the relevance of the maqāṣid al-sharī‘ah approach. This research employs a field research method with a descriptive qualitative approach. Data were collected through observation, in-depth interviews, and documentation involving relatives of unregistered marriage actors, officials of the Office of Religious Affairs (KUA), and community leaders. The findings reveal that, normatively, the state has established adequate legal instruments governing marriage, particularly regarding mandatory registration as a form of legal protection. However, in practice, there remains a gap between legal norms and social realities, where people tend to prioritize religious validity over administrative registration. Socio-cultural factors and low legal awareness significantly influence the preference for unregistered marriages. Furthermore, from the perspective of maqasid al-shari‘ah, unregistered marriage practices are considered inconsistent with the objectives of protecting life, lineage, and property, as they potentially harm women and children. Therefore, marriage registration is viewed as a crucial instrument in ensuring family welfare. This study highlights the need for integrating state legal norms with social values through strengthening legal literacy and institutional roles.